Acute respiratory infections control in the context of the IMCI strategy in the Americas - Benguigui,Yehuda (2003)
Acute respiratory infections (ARI) are an important cause of morbidiyty and mortality in children all over the World, particularly in developing countries. Contrasts in mortality can be observed among the countries in America, and also within the countries. Contrasts are also observed in morbidity, associated with differences in nutritional status, absence of breast-feeding and characteristics of care given for ill chidren. Parents perception of disease, patterns and habits of care administered to child during the illness, level of concern about decision to seek assistence, manner in wich care is sought and extent to wich recommendations are followed have great influence in the course and outcome of the disease. Bacterial resistance to antibiotics is an increasing problem in America, with an average of 26,1% resistance of Streptococcus pneumonia to penicilin. Antibiotics are frequently used in irrational way, and up to 70% of ARI receive antibiotics unnecessarily. Controlling IRA has become a priority. Preventive interventions with vaccines, specially current conjugate vaccines against Haemophilus influenzae and Streptococcus pneumoniae, and standardized case management, as proposed by Integrated Management of Childhood Ilness (IMCI) seems to be the most important steps for this public health problem.